Caminhabilidade como instrumento de mobilidade urbana: um estudo de caso em Belo Horizonte - Izabela Ribas Vianna de Carvalho (2018)
Like other major Brazilian cities, Belo Horizonte was shaped under a model of urbanization that favors individual motorized vehicles. This course led to consequences for the conditions of pedestrian movements, resulting in the neglect of the foot mode as a form of transport. Despite the efforts made to increase the pedestrian infrastructure in some regions of the municipality during the last years, there is still a long way to go to make the streets of Belo Horizonte more pedestrian friendly, as well as for the recognition of foot mode as a contributor to the sustainability and health of society. Therefore, it is necessary to understand the pedestrian environment through the development and application of methodologies that aid in decision making, which foster conditions for people to feel invited to move, stay and socialize in the streets, thus reconstituting the physical and social space. The walkability index is an evaluation tool of the built environment, from the point of view of the pedestrian, where characteristics, often subjective, are transformed into objective data, allowing a better understanding of the quality of a spatiality. In this context, this research aims to develop a walkability index to enable the evaluation of the walking environment of Belo Horizonte. The index was constructed in two steps. Firstly, indicators were selected based on the most recurrent attributes in the literature (national and international), as well as their respective measurement criteria of the walkability. Next, attributes that were considered representative of specific characteristics of Belo Horizonte were incorporated in addition to those already previously selected. The final index consists of a set of 27 indicators: 24 for the analysis of sidewalk segments and 3 for the analysis of crossings. The evaluation methodology was is easy and intuitive, considering whenever possible the qualitative analysis of the elements so that the method is accessible and quick to execute. The developed index was used to evaluate a composite spatiality of 21 segments and 26 crossings in the Carlos Prates neighborhood, Belo Horizonte. The index was efficient for the evaluation of the walkability of Belo Horizonte at the microscale, being able to be used for the analysis of a segment, street or a small area. The use of the index in the analysis of urban requalification projects was also useful in the evaluation of proposals under the perspective of pedestrians, making it possible to validate projects, as well as propose possible course corrections.